Mechanical and Structural Characterization of Resole Resin Composites Reinforced with Sabai Grass-Derived Cellulose Fibers - Puri, Aabha; Adhikari, Rameshwar; Pandit, Rajesh (Journal of Nepal Chemical Society, 2024)
Cellulose fibers were extracted from Sabai grass (Eulaliopsis binata) using mechanical and chemical treatments. The grass was ground to ~250 µm powder and bleached with hydrogen peroxide and acetic acid. The bleached fibers were treated with 6% sodium hydroxide solution and incorporated into resole resin at various weight percentages to prepare the composites. The prepared samples were characterized by X-ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), and compressive strength tests. The XRD and FTIR showed a nanometric crystallite size of 3.84 nm and effective removal of non-cellulosic compounds, respectively, leading to a compressive strength increase from 15.60 MPa to 25.26 MPa at 3 wt.-% cellulose fiber. The compressive strength improved up to 3 wt.-% cellulose fiber, which however declined upon adding more filler. SEM revealed modified surface morphology in the composites with cellulose fibers.